Materials and processes for the optical Additive Manufacturing of advanced organic/inorganic nanocomposites for the mask-less plating of insulator and semiconductor substrates, and microfluidic devices - Di Cianni, Wera; Cipparrone, Gabriella; Giocondo, Michele; De Luca, Antonio; De Leon, Alberto Sanz (Università della Calabria, 2020)
The research presented in this doctoral thesis is carried out in the nanotechnology and soft matter frameworks, under the 4.0 Industry paradigm, inspired by the need to find new strategies for the Additive Manufacturing (AM) and to obtain new processable nanocomposites with enhanced properties. The AM technologies allow to build 3D objects with complex geometries by adding layer-upon-layer of material without any mold and permits to fabricate structured objects and microfluidic systems with particular optical and mechanical properties which cannot be easily made with classical Subtractive Manufacturing (SM) techniques. This paves the way to large improvements in optoelectronics, biotechnology, diagnostic or medicine. Moreover, the combined employment of bottom-up and top-down fabrication approaches could lead to important advances in the field of nanotechnology, widening further the possible applications field, permitting high resolution repeatable nanofabrication of 3D complex objects with the possibility of immediate industrial applications. The first AM technique used in this work is Stereolithography (SL), a vat photopolymerization technique that uses UV light to produce objects with resolution in the range 10-100 μm. Here, the novelty consists in adding a metallic precursor (KAuCl4) to a typical photosensitive resin to produce nanocomposites with gold nanoparticles synthesized in situ via photo- and thermal reduction. Nanocomposites produced are rich in gold nanoparticles and have interesting optical and plasmonic properties. Moreover, a fine tuning of the concentration of the gold salt allows the resin polymerization without suffering any inhibition of the gold precursor. A similar approach, taking advantage of the combination with photoreduction of a gold precursor (HAuCl4), can be achieved using a different technique belonging to the vat photopolymerization category, namely the Two Photon Direct Laser Writing (TP-DLW). This technique exploits the optical, nonlinear multiphoton absorption process and allows for the fabrication of 3D objects featuring details below the diffraction limit, down to 100 nm or even less. Here, this multiphoton absorption process is exploited to trigger the photo-reduction of the gold precursor. The use of a transparent hydrogel matrix allows for a fine control of the nanoparticles’ growth on either transparent or opaque substrates, such as glass or silicon, without the need of using masks or molds. An in-depth study on the diffusive process underlying the nanoparticles growth and a control of the ionic concentration are done to prove the importance of having a polymeric network to hold the created nanoparticles at their place, which enhances the quality of the created nanostructures. The nanofabrication of fiber reinforced polymer nanocomposites by TP-DLW was also demonstrated. For these experiments, the classical glass or silicon substrates were replaced with a silicon substrate on which silica nanowires (SiO2 NWs) have been previously grown. This research allowed to achieve the best resolution offered by the TP-DLW technique, even with high loads of fillers of SiO2 NWs, up to 70 wt%. This was achieved by matching the refractive indices of the SiO2 NWs and of the photoresist used as polymeric matrix. These nanocomposite materials presented a noticeable improvement of nano-hardness and elastic modulus when compared to the pristine photoresist, indicating how the proposed technique is well-suited for nano-applications with higher structural requirements, as in advanced microfluidics. A final comparison of the AM technologies used in the thesis is done to elucidate the advantages and disadvantages of each one of these techniques to choose the most efficient, easiest and fastest, depending on the materials to be used or the required resolution.
Dottorato di ricerca in Scienze e tecnologie fisiche, chimiche e dei materiali. Ciclo XXXIII
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics::Atomic and molecular physics